Implementation of the Inquiry Learning Model to Improve Students' Science Learning Outcomes at MIS Arul Relem - Kasidah; Putri, Erlina (MANDAILING GLOBAL EDUKASIA, 2025)
This research addresses the challenge of low student engagement and unsatisfactory achievement in Science (IPA) among fifth-grade students at MIS Arul Relem. The underlying issue identified was the passive learning approach, which contributed to low motivation and poor conceptual understanding. The study aims to determine the extent to which the application of the Inquiry Learning Model can effectively improve these Science learning outcomes. The research employed a Classroom Action Research (CAR) design, conducted over two sequential cycles. The participants were the entire population of fifth-grade students, totaling 25 individuals. Data collection instruments included a pre-test, post-tests for each cycle, and student and teacher activity observation sheets. The success criterion for the intervention was set at an 80% student mastery rate with a Minimum Completeness Criterion (KKM) score of 70. The results demonstrated significant improvement. In the initial pre-cycle phase, the class average score was 60, with only 40% of students achieving mastery. Following the implementation of the Inquiry Learning Model in Cycle I, the class average increased to 75, and the mastery percentage rose to 68%. By the conclusion of Cycle II, the class average reached 82, and the learning mastery dramatically surged to 88%, successfully surpassing the established success criterion. Furthermore, observation data confirmed a noticeable increase in student activity and enthusiasm during the learning process. In conclusion, the Inquiry Learning Model is proven to be a highly effective and appropriate strategy for enhancing Science Learning Outcomes and fostering active participation among fifth-grade students at MIS Arul Relem.